The Role of Illicit Drug Use in Family and Domestic Violence in Australia. Issue 15 (August 2021) - Coomber, Kerri; Mayshak, Richelle; Liknaitzky, Paul; Curtis, Ashlee; Walker, Arlene; Hyder, Shannon; Miller, Peter
Drug use has been shown to interact in complex ways with the occurrence and prevalence of family and domestic violence (FDV), with illicit drug use being associated with an increased risk for FDV. The current study aims to extend upon the literature by investigating the role of illicit drugs in intimate partner violence (IPV), family violence (FV), and other violence (violence between people other than partners or family) within a representative Australian sample ( n = 5, 118). Participants were recruited through an online survey panel and completed an online self-report survey assessing the role of alcohol and other drugs on violence, with a specific focus on FDV. Binary logistic regression showed that respondents who reported having used any illicit drug in the past 12 months (with or without alcohol use) had over three times the odds of experiencing any violence in the past 12 months (OR = 3.18, 95% confidence interval (CI) = [2.25, 4.48]) compared with those not using illicit drugs. Furthermore, drug involvement in FDV (IPV or FV) was significantly more likely than other violent incident types (OR = 1.65, 95% CI = [1.25, 2.19]). For the most recent FDV incident, age group was the only significant demographic predictor of drug involvement at this incident; younger age groups were over twice as likely to report drug involvement than those over 65 years of age. Drug involvement at the most recent FDV incident was also associated with over twice the odds of injury (OR = 2.38, 95% CI = [1.67, 3.38]) and significantly greater negative life impact. The findings that drug use increases both the risk for and impact of FDV indicate the need for policy that advocates for interventions addressing both drug use and violence in combination.